AlF3 reaction mechanism and its influence on α-Al2O3 mineralization. Issue 8 (June 2016) - Riello, D.; Zetterström, C.; Parr, C.; Braulio, M.A.L.; Moreira, M.; Gallo, J.B.; Pandolfelli, V.C.
Abstract: Calcination is an important step in the alumina production process, affecting the final properties of the attained product, such as the surface area, soda and alpha phase contents, morphology and primary crystal size. Over the previous decades, attempts have been made to understand this process aiming to decrease the temperature and time of calcination. Considering this, the use of mineralizers, such as fluorides, is a well-known practice, as these additives act decreasing the activation energy for the transformation from the transition to alpha alumina phase. However, the actual reaction mechanism is not well understood. In this study, the likely mechanism was investigated by DTA-TG-MS for samples containing 3 wt% of AlF3 in a transition alumina and a hydrate. The emission of HF gas during the alpha transformation pointed out a gas–solid reaction via the generation of a transition compound (Al–O–F). Physico-chemical properties such as the surface area, alpha content, primary crystal size and morphology were also investigated for 0.45 and 0.6 wt% AlF3 addition for the different precursors. Additionally, the influence of the homogenization step in the alpha formation was studied. The results highlighted that a lower amount of AlF3 can be used if there is a good confinement of gases inside the furnace.